Effect of Wall Material on H– Production in a Plasma Sputter-Type Ion Source - Ponce, Y. D. M.; Lazarte, J. R. S.; Ramos, H. J. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 16 No 2 (2004), 2007)
The effect of wall material on negative hydrogen ion (H–) production was investigated in a multicusp plasma sputter-type ion source (PSTIS). Steady-state cesium-seeded hydrogen plasma was generated by a tungsten filament, while H– was produced through surface production using a molybdenum sputter target. Plasma parameters and H– yields were determined from Langmuir probe and Faraday cup measurements, respectively. At an input hydrogen pressure of 1.2 mTorr and optimum plasma discharge parameters Vd = –90 V and Id = –2.25 A, the plasma parameters ne was highest and T–e was lowest as determined from Langmuir probe measurements. At these conditions, aluminum generates the highest ion current density of 0.01697 mA/cm2, which is 64% more than the 0.01085 mA/cm2 that stainless steel produces. The yield of copper, meanwhile, falls between the two materials at 0.01164 mA/cm2. The beam is maximum at Vt = –125 V. Focusing is achieved at VL = –70 V for stainless steel, Vt = –60 V for aluminum, and Vt = –50 V for copper. The results demonstrate that proper selection of wall material can greatly enhance the H– production of the PSTIS.